Analisis Pengaruh Literasia Digital, Pengalaman Teknologi, dan Faktor Psikologis terhadap Kesiapan Mahasiswa Akauntansi Kolaborasi dengan Cloud Accounting - Ruth Septiana Sinaga (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The development of digital technology has brought significant changes to accounting practices, including the emergence of cloud accounting, which is now widely used by various companies. In this context, accounting students as prospective professionals need to have adequate readiness to face this digital transformation. This study aims to determine the extent of the influence of digital literacy, technology usage experience, and psychological factors (especially technology anxiety) on students' readiness to face the use of cloud accounting. This research uses a quantitative approach by distributing questionnaires online to active students in the Accounting Study Program at Universitas Dian Nuswantoro Semarang. The number of respondents successfully collected was 436 people, determined based on the Cochran formula and the Krejcie and Morgan table. The data obtained have undergone validity and reliability tests, as well as meeting normality assumptions for further analysis using linear regression. The research results show that digital literacy and technology experience have a positive and significant impact on student readiness. Conversely, the psychological factor of anxiety towards technology shows a negative but still significant influence. Of the three variables, digital literacy is the most dominant factor. These results emphasize the importance of enhancing digital competencies and familiarizing with technology from an early age so that students are better prepared to face professional challenges in the digital era.